2002
DOI: 10.1002/ajpa.10182
|View full text |Cite
|
Sign up to set email alerts
|

Canalization, developmental stability, and morphological integration in primate limbs

Abstract: Canalization and developmental stability refer to the tendency of developmental processes to follow particular trajectories, despite external or internal perturbation. Canalization is the tendency for development of a specific genotype to follow the same trajectory under different conditions (different environments or different genetic backgrounds), while developmental stability is the tendency for the development of a specific genotype to follow the same trajectory under the same conditions. Morphological int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
342
3
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(399 citation statements)
references
References 169 publications
(173 reference statements)
33
342
3
4
Order By: Relevance
“…We found no significant correlations within individuals between asymmetry in bone lengths and asymmetry in diaphyseal breadths, supporting their relative independence. This suggests that lengths and diaphyseal breadths are ''modular'' in the sense of independent development, or perhaps simply that developmental integration of limb lengths and breadths is overridden to different extents by subsequent, stronger environmental effects on breadths (for a general discussion, see Hallgrímsson et al, 2002). It may be that, although limbs are potentially subject to the same perturbations during development, differing degrees of canalization (Hallgrímsson et al, 2002(Hallgrímsson et al, , 2003 may leave some bone dimensions more sensitive to these effects both in utero and after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no significant correlations within individuals between asymmetry in bone lengths and asymmetry in diaphyseal breadths, supporting their relative independence. This suggests that lengths and diaphyseal breadths are ''modular'' in the sense of independent development, or perhaps simply that developmental integration of limb lengths and breadths is overridden to different extents by subsequent, stronger environmental effects on breadths (for a general discussion, see Hallgrímsson et al, 2002). It may be that, although limbs are potentially subject to the same perturbations during development, differing degrees of canalization (Hallgrímsson et al, 2002(Hallgrímsson et al, , 2003 may leave some bone dimensions more sensitive to these effects both in utero and after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, forearm loading is also shared between the radius and ulna, but any variation in ulnar bilateral asymmetry (not measured in this study) apparently does not negate asymmetry correlations between the humerus and radius. The ipsilateral correlations of asymmetry in bone length in both the upper and lower limbs may relate to developmental mechanisms of control over bone length within limbs, although experimental support for this is equivocal (Hallgrímsson et al, 2002). Further investigations of modularity and morphological integration during development may elucidate the covariation of bilateral asymmetry between different types of traits and regions of the limbs and the interaction between genetic and environmental (particularly mechanical) influences on these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it has been suggested that the low bone-volume fraction observed in human thoracic vertebrae and the first and second metatarsals are the result of systemic physiological differences between humans and apes (14,16). These studies do not suggest the mechanism or the function of this systemic gracility, but one potential explanation may be selection for increased tissue economy in hominins (5,(33)(34)(35).…”
Section: Significancementioning
confidence: 99%
“…Nonetheless, quantitative approaches can estimate the developmental contribution to phenotypic integration in fossil taxa, even without identifying a specific developmental driver, by measuring fluctuating asymmetry (FA). Simply, whereas genetic and environmental perturbations affect symmetric traits similarly, developmental errors lead to random, nondirectional asymmetries in the morphology, thereby revealing patterns of direct developmental interactions among traits (22,(46)(47)(48)(49). By quantifying FA, one can test whether the patterns of direct developmental interactions correspond to major components of variation across individuals and among taxa, as would be expected if developmental integration is a significant constraint on evolutionary variation.…”
Section: Significancementioning
confidence: 99%